Identification of Soil and Water Conservation Technologies Used on Different Landscape Positions in Maziba Sub-catchment - Ndemere, Julius; Mary makokha; Tenywa Moses (Kabale University, 2018)
Abstract. Soil and water resources are important for sustaining life on earth since they are the main components of sub-catchments. Despite the technologies that have been introduced in Maziba sub-catchment, farmers have variations in technology acceptance due to over cultivation of land, population pressure, and deforestation that accelerate soil erosion. The objective of the study was to characterize soil and water conservation technologies used at different landscape positions by farmers in Maziba sub-catchment. Descriptive statistics were used to analyze soil and water conservation technologies practiced in the study area. Probability sampling technique was used to select research respondents, who were selected to obtain predominantly used soil and water conservation technologies data, using semi-structured questionnaire. Statistical analysis of the data collected was done using special packages for social scientists (SPSS 17.0) statistical software and Microsoft Excel 2007. The study revealed that terracing (35%), mulching (21%) and trenching (13%) were the predominant soil and water conservation technologies reported. The study recommended formal education for non-educated farmers since the level of education influenced the use of soil and water conservation technologies in the study area